Implementasi Supervisi Akademik Kepala Sekolah Dalam Meningkatkan Kompetensi Pedagogik Guru di SMPIT Mutiara Ilmu Bangkalan - Hanaris, Fitria (Program Studi Manajemen Pendidikan Islam, 2025)
This study aims to analyze the implementation of academic supervision by the school principal in enhancing teachers' pedagogical competence at SMPIT Mutiara Ilmu Bangkalan. The research is driven by the phenomenon of